2015
DOI: 10.1007/s00376-014-4098-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and evaluation of the global aerosol optical properties simulated by an online aerosol-coupled non-hydrostatic icosahedral atmospheric model

Abstract: Aerosol optical properties are simulated using the Spectral Radiation Transport Model for Aerosol Species (SPRINTARS) coupled with the Non-hydrostatic ICosahedral Atmospheric Model (NICAM). The 3-year global mean all-sky aerosol optical thickness (AOT) at 550 nm, theÅngström Exponent (AE) based on AOTs at 440 and 870 nm, and the single scattering albedo (SSA) at 550 nm are estimated at 0.123, 0.657 and 0.944, respectively. For each aerosol species, the mean AOT is within the range of the AeroCom models. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
0
11
1
Order By: Relevance
“…As a result, the input parameters used for aerosol SSA calculations are variable and depend on the corresponding measurements, which can cause a wide range of calculated aerosol SSAs. For example, some 5 previous global modeling studies found that no significant bias existed between calculated SSAs versus Aerosol Robotic Network (AERONET) observations (Chin et al, 2009;Dai et al, 2015), while other studies showed positive biases in the estimates (Feng et al, 2013;Jo et al, 2016;Lin et al, 2014;Myhre et al, 2009). We surmised that the SSA bias could be reduced when models use relatively high BC emissions and a low BC density.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…As a result, the input parameters used for aerosol SSA calculations are variable and depend on the corresponding measurements, which can cause a wide range of calculated aerosol SSAs. For example, some 5 previous global modeling studies found that no significant bias existed between calculated SSAs versus Aerosol Robotic Network (AERONET) observations (Chin et al, 2009;Dai et al, 2015), while other studies showed positive biases in the estimates (Feng et al, 2013;Jo et al, 2016;Lin et al, 2014;Myhre et al, 2009). We surmised that the SSA bias could be reduced when models use relatively high BC emissions and a low BC density.…”
Section: Introductionmentioning
confidence: 59%
“…3. The modelled SSA calculations from previous studies were mostly evaluated between 440 -550 nm (Dai et al, 2015;Jo et al, 2016;Lin et al, 2014). However, SSAs at both shorter and longer wavelengths should be evaluated together for the model evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The large positive BIAS and RMSE of the CONTROL experiment over Australia, which are mainly caused by the overestimation of dust aerosol, are also removed by the assimilation of the Himawari‐8 AOTs. The CONTROL experiment tends to underestimate the AOTs over India and most of the ocean regions (Dai et al, ), and all of the analyses correctly increase the AOTs to better match the observations. In Figure , we further plot the straightforward comparisons of the simulated monthly mean hourly AOTs in the experiments of the CONTROL, 4D‐LETKF‐6H, and 4D‐LETKF‐24H to those in the LETKF, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest anthropogenic and biomass burning emissions are found over the North China Plain (NCP) and North Australia, respectively. The emission fluxes of dust and sea salt are both calculated online (Dai, Goto, et al, ; Dai et al, ; Dai et al, ; Takemura et al, ) and are mainly dependent on the near‐surface wind speed.…”
Section: Aerosol Data Assimilation System and Methodologymentioning
confidence: 99%
“…In numerical models, the extinction of light is usually quantified with the integration of scattering and absorbing effects of the particles (e.g., Takemura et al, 2002;Goto et al, 2011;Dai et al, 2015). Major aerosol types included in the models are carbonaceous, sulfate, soil dust, and sea salt (e.g., Takemura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%